(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The advancement of the economy is significantly impacted by the activities of the pharmaceutical industry. This investigation's objective is to ascertain the degree to which workers at various drug companies are content with their jobs and the role that they play in the company. The major emphasis of this inquiry is on the relevance of the phrase "occupation fulfilment factors" and the influence that these aspects have on the overall sense of job satisfaction experienced by representatives. The pharmaceutical industry's representatives have progressed to the advantageous stage of the summative task fulfilment procedure. The current evaluation gives an update on the level of job satisfaction that is now held by representatives of various pharmacy organisations and analyses some of the issues that have come up as a result. The aim of the study are to examine the Profile of the sample respondents in examined area and to determine the elements that impact employee work satisfaction .A descriptive research design combined with a survey methodology was used. For the aim of this study, the researcher has drawn from the primary and the secondary bodies of information. The secondary data were gathered from a variety of resources, including books, periodicals, articles, research projects, and websites. The period of the data collection was done through the Google forms during September 2021. Convenient sampling technique was applied to collect the primary data from 120 sample respondents As a direct result of the continued expansion that the pharmaceutical industry in India is experiencing at the present time, research has primarily begun to investigate the significance of a number of factors, including compensation and advancement opportunities, working climate and conditions, employer stability, worker relationship, and reasonableness in terms of work fulfilment.